(untitled) (The International Journal for Scientific Research, 2024)
Sports management is a vital area that plays a crucial role in the development and management of sports activities at the national and international levels. The administrative structures of sports institutions are witnessing increasing challenges, exacerbated by sporting developments and important events that have occurred in the global sports scene, among which is what happened in 2015 in the context of scandals and abuses that followed. (Bishop & Cooper, 2018a) The 2015 FIFA events, which were related to corruption scandals and ethical abuses within the international sports body, cast a shadow over the various sports management structures. The impact of these events was not only local, but extended to international dimensions, igniting the need to reconsider and improve sports management structures in light of scientific standards in the field of sports leadership. (Rowe, 2017b) This study aims to explore and analyse in depth the changes that can be achieved in sports management structures, particularly in the context of leading the engineering of the operations of national and international sports organizations. Emphasis will be placed on reviewing the relevant scientific literature and analysing current management structures to provide a comprehensive assessment of the positive and negative impacts that resulted from the events of FIFA 2015. This study also proposes amendments to sports management structures, based on doctoral and master’s standards in sports leadership, with the aim of improving the effectiveness of these structures in crisis management and achieving the objectives of sport in a more comprehensive and robust manner.